Evaluating outcomes of percutaneous nephrolithotomy (PCNL) - جبيلي مجد; لؤي نداف; أيمن حرفوش (Latakia University Journal -Medical Sciences Series, 2024)
Objective: Urinary stone disease is the third most common urinary system disease. Laparoscopic surgery (PCNL) is one of methods of treating large kidney stones, which is less invasive than others. The aim of research is evaluating outcomes of percutaneous nephrolithotomy (PCNL) Methods:The research sample consisted of (52) patients in the period between 1/8/2019 – 1/8/2021 at Tishreen University Hospital in Latakia. The patients were divided into two groups:1st group: The stone size 2 to 4 cm, 2nd group > 4 cm, Guy Score used to study location of the stone. Clavien dindo classification used to study complications of PCNL. Results: The research included 52 patients .The stone-free rate reached 82.7% of sample, while 17.3% had residual stones (greater than 6 mm). Although the success rates were lower at a stone size larger than 4 cm compared to the other group (2-4 cm in size), there were no significant differences regarding the size of the stone and the result of the procedure .The percentage of complications was 21.1%.11.5% of them are primarily G1 and we have not observed any cases in the fourth and fifth grades Bleeding (5.7%), fever and urinary tract infection (3.9%).All patients with G1 and G2 complications were managed with appropriate conservative treatment, patients with G3 complications were treated by performing ureteroscopy and installing DJ ureteral catheterization with subsequent follow-up. The percentage of complications occurring according to the clavien dindo classification increased with increasing stone size, with p-value = 0.01. The percentage of complications occurring according to the clavien dindo classification also increased according to the location of the stone with increasing grade, with statistically significant differences with p-value = 0.0001. Conclusion: The percutaneous endoscopic removal of large renal stones (PCNL) is an effective method with minimal trauma and complications.